Plumage Uniformity, Growth Rate and Growth Hormone Polymorphism in Indonesian Hybrid Chickens - Perdamaian, I.V. Utama, A.B.I.; Daryono , B.S. (International Journal of Poultry Science, 2018)
Background: The native Indonesian chicken, the Pelung, is widely known as a preferred source of meat and eggs but it has the disadvantage of relatively slow growth. Recently, ♂Pelung chickens were crossed with ♀ F1 chickens (♀ Pelung×♂ Broiler chicken) to generate the first back-crossed (BC1) chicken for use as a new breed. Molecular markers were observed within the Growth hormone (Gh) gene. Avian Gh (AY461843) is one of the most important genes influencing growth-related traits; specifically, the Gh intron 3 Single Nucleotide Polymorphism (SNP) G+1705A is significantly associated with the growth traits of Chinese chicken breeds. This study aimed to produce a new, fast-growing chicken line that is more homozygous for morphological traits than its parents and to observe the Gh  gene intron 3 SNP G+1705A polymorphism in this BC1 chicken. Methodology: Day-old chickens (DOCs) were intensively reared for 7 weeks and weighed weekly. Qualitative and quantitative characteristics and the Feed Conversion Ratio (FCR) of the BC1 chickens were determined at the seventh week of observation. Restriction Fragment Length Polymorphism (RFLP) analysis was performed to detect genotype differences among the BC1 populations. Results: In both sexes, weight gain was faster in the BC1 chickens (919.9 grams) than in the Pelung chickens (434.74 g) but lower than in the broiler (1.500 g) chickens. The FCR for the BC1 line (2.32) was between that of the Pelung (3.35) and broiler (1.55) chickens. The BC1 hybrid chicken genotype was 89% dominant homozygous (GG) and 11% heterozygous (GA). Conclusion: In this study, the body parameters did not significantly differ among the genotypes (GA and GG). The BC1 chicken was deemed satisfactory for use as a meat chicken.